Α-decay chains and cluster radioactivity of 295−299119 and 298−302120 isotopes using zero- and finite-range NN interactions. (24th May 2019) - Ismail, M; Adel, A
Abstract: The α -decay half-lives of the superheavy nuclei (SHN) with Z  = 119 and 120 are investigated by employing the density dependent cluster model. Within the double-folding model, the α -nucleus interaction potential is calculated microscopically using a realistic nucleon–nucleon (NN) interaction. The exchange part of the interaction potential is evaluated within a local density formalism, using the finite-range as well as the ordinary zero-range exchange components of the NN interaction. The influence of nuclear deformation is presented. The calculated values of α -decay half-lives for five isotopes of each of the SHN with Z  = 119 and 120 have been compared with those values evaluated using other theoretical models. It was found that our theoretical values are in good agreement with their counterparts. The competition between α -decay and spontaneous fission is investigated and predictions for possible decay modes for the unknown nuclei 295−299 119 and 298−302 120 are presented. The probable cluster decay half-lives of 295 119 and 298 120 have been studied within the previously mentioned double-folding model as well as the unified formula (UF) of half-lives for α decay and cluster radioactivity, the scaling law by Horoi (Horoi) and the universal decay law (UDL). The cluster decay half-lives derived from the former three models are too large compared to α -decay half-lives, but the UDL formula predicts the possibility of heavy cluster emission. The mass number variations of the microscopic shell correction energy for different α -decay chains of Z  = 119 and 120 isotopes are presented. The possible correlations between the shell effect and each of α -decay and cluster decay half-lives are discussed. We hope that the proposed theoretical predictions for α -decay chains and cluster radioactivity provide a new perspective to experimentalists.